PENGARUH PENANAMAN MODAL ASING TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA : ANALISIS DATA PANEL PERIODE 1994-2013 - Jefry Batara Salebu (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2014)
This study analyze the effect of foreign direct investment (FDI) on economic growth in indonesia. Panel data of 20 subsector for period 1994-2013 obstaining a balanced panel of 340 observations are used in the empirical estimation. The fixed effect model is the best model based on redundant fixed effect test and correlated random effect Housman test to find the significant impact of FDI on economic growth. The empirical result show strong evidence that LPDI has a significant and positive influense on LGDP. Based on the result of the regression, it could be said that FDI will boost economic growth in indonesia . howewer , it was found that not all subsector of FDI have a significant positive effect on economic growth. There are only four sectors where LFDI has significantly and positively impact to LGDP. This the four sectors of the FDI have considerable influence on economic growth in Indonesia, so that some supports from the government of Indonesia are needed in this sector, for example tax incentive regulation. To attract FDI from these subsector to invest in Indonesia.